Peran Zakat terhadap Kemiskinan Ditinjau dari Jenis Pendistribusian Zakat - Atasoge, Immawan Ben Azhar; Andiansyah, Farma; Asyrofi, Imam; Monada, Fani (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
Poverty is a social economic and political problem in Indonesia. The Central Agency on Statistics reported that Indonesia's poor population in 2019 was 9.41%, equivalent to 25.14 million people. Zakat is one of the Islamic social finance instruments which has an important role in poverty alleviation efforts. The Indonesian government through the Indonesian’s National Zakat Agency (BAZNAS) has issued various programs in an effort to alleviate poverty in Indonesia. This study aims to test the effectiveness of the zakat fund distribution programs by BAZNAS in reducing poverty levels in Indonesia. This research uses OLS (Ordinary Least Square) method. Research using Secondary Data in the form of Monthly data for the period of 2011-2019. This study found that zakat distribution programs in the social and educational sectors have a significant negative effect on poverty levels in Indonesia.